ERA OF NEW ANTICOAGULANTS IN THE TREATMENT OF NON-VALVULAR ATRIAL FIBRILLATION: PROSPECTS AND CHALLENGES - Z. M. Safiullina; S. V. Shalaev (Столичная издательская компания, 2015)
Studies data on new anticoagulants, direct oral thrombin inhibitor (dabigatran) and direct inhibitors of coagulation factor Xa (rivaroxaban, apixaban), in the treatment of nonvalvular atrial fibrillation are presented. Effects of these drugs on cardiovascular events in atrial fibrillation are analyzed based on the results of various studies. Prospects for further research are discussed.